Imperialism and the Rhetoric of the Threat: Islamic Fundamentalism in Western Scholarship - Ali Munhanif (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2000)
The way in which Western scholars understand the nature of religion and the relationship of religion to politics and society greatly determine their expectations and judgements.